IMF Survey : Volume 29, Issue 17. (IMF Survey; IMF Survey ;, 2000)
In a press release issued on August 18, the IMF Executive Board announced that on August 3 it had discussed making the independent Evaluation Office operational (see Press Release No. 00/27) and agreed to the publication of the background paper that provided the basis for the discussion, as well as the Chairman's concluding remarks.